The Use of Social Networking Sites (SNSS) in EFL Secondary Education: A Systematic Review - Salam, Urai; Apriska, Cyntia; Rezeki, Yanti Sri; Ramli, Nor Fazlin Mohd (Journal of Languages and Language Teaching, 2025)
This study provides a comprehensive systematic review of the integration of five major social networking sites (SNSs)—Facebook, YouTube, WhatsApp, Instagram, and TikTok—within secondary English as a Foreign Language (EFL) education. Using the Harzing Publish or Perish software, over 1,500 journal articles published between 2018 and 2023 were screened, with 87 meeting the inclusion criteria for in-depth analysis. The findings reveal a growing research interest in this area, with an average effect size of 1.792, indicating a significant impact. YouTube emerged as the most frequently examined platform, featured in 36 studies, while the SNSs overall were applied in diverse ways, including as media resources, learning management systems (LMS), discussion forums, and platforms for content creation. Results suggest that SNS integration can enhance learner engagement, promote student-centered and blended learning, and foster both language proficiency and digital literacy through interactive and creative practices. Future research should investigate the comparative effectiveness of different platforms, assess their long-term contributions to EFL education, and consider emerging trends such as GenAI-based applications.